2012
DOI: 10.1111/j.1471-4159.2012.07898.x
|View full text |Cite
|
Sign up to set email alerts
|

Swim training attenuates oxidative damage and promotes neuroprotection in cerebral cortical slices submitted to oxygen glucose deprivation

Abstract: Although it is well known that regular exercise may promote neuroprotection, the mechanisms underlying this effect are still not fully understood. We investigated if swim training promotes neuroprotection by potentiating antioxidant pathways, thereby decreasing the effects of oxidative stress on glutamate and nitric oxide release. Male Wistar rats (n=36) were evenly randomized into a trained group (TRA) (5 days/week, 8 weeks, 30 min) and a sedentary group (SED). Forty-eight hours after the last session of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…; Leite et al . ). The exercise would have to be much more intense (close to maximum workload capacity) to induce significant changes in physiological variables associated with stress (Scopel et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Leite et al . ). The exercise would have to be much more intense (close to maximum workload capacity) to induce significant changes in physiological variables associated with stress (Scopel et al .…”
Section: Discussionmentioning
confidence: 97%
“…In fact, our group has already shown that regular physical exercise sessions are able to decrease glutamate and nitrite release as well as membrane damage in the OGD cortical slices (Leite et al . ). Therefore, physical exercise may result in an improvement of neuronal ability to endure energetic depletion, as well as the changes of apoptosis regulation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Physical training impacts several body systems including cardiovascular, musculoskeletal and nervous system ( 1 ). Studies have showed that regular exercise improves brain health and prevents or improves recovery from brain injuries ( 1 ) by enhancing neurotrophic factor levels ( 2 ) and modulating oxidative status ( 1 ).…”
Section: Introductionmentioning
confidence: 99%